The Ecobiology of Toroviruses (Tobaniviridae) and Their Association with The Enteric Diseases in Animals and Humans - Mohd Iswadi, Ismail (INTI International University, 2023)
Torovirus (ToV) is one of the responsible for causing gastroenteritis diseases in animals and humans worldwide. Since its discovery in the 1970s, ToVs remained one of the important causative agents for gastroenteritis and diarrhoea in horses, cattle, sheep, goats, pigs, and other animals including humans. Therefore, the ecobiology and association of ToVs in animals and humans remained to be elucidated. The molecular basis of ToVs in animals and humans has been well described. ToVs can be recognised as enveloped viruses with non-segmented and positive-sense of RNA genome, and pleomorphic shape. In addition, the recent epidemiology, clinical signs, diagnostic methods, and suitable prevention and control measures are also explained in this review. Clinical signs of ToV infection are vary; these include pyrexia, diarrhoea, dehydration, lethargy, depression, and death. Various diagnostic methods were used in the detection of ToVs such as electron microscopy, RT-PCR, haemagglutination inhibition, ELISA, and neutralisation assay. At present, no vaccine is available for ToV, but the virus can be prevented by applying good hygiene, strict biosecurity, and proper sanitary conditions.